Do Wikipedians follow domain experts? A domain-specific study on Wikipedia contribution - ZHANG, Yi (Institutional Knowledge at Singapore Management University, 2010)
Wikipedia is one of the most successful online knowledge bases, attracting millions of visits daily. Not surprisingly, its huge success has in turn led to immense research interest for a better understanding of the collaborative knowledge building process. In this paper, we performed a (terrorism) domain-specific case study, comparing and contrasting the knowledge evolution in Wikipedia with a knowledge base created by domain experts. Specifically, we used the Terrorism Knowledge Base (TKB) developed by experts at MIPT. We identified 409 Wikipedia articles matching TKB records, and went ahead to study them from three aspects: creation, revision, and link evolution. We found that the knowledge building in Wikipedia had largely been independent, and did not follow TKB - despite the open and online availability of the latter, as well as awareness of at least some of the Wikipedia contributors about the TKB source. In an attempt to identify possible reasons, we conducted a detailed analysis of contribution behavior demonstrated by Wikipedians. It was found that most Wikipedians contribute to a relatively small set of articles each. Their contribution was biased towards one or very few article(s). At the same time, each article's contributions are often championed by very few active contributors including the article's creator. We finally arrive at a conjecture that the contributions in Wikipedia are more to cover knowledge at the article level rather than at the domain level.